Implementation Strategy of Electronic-Based Goods and Services Procurement (E-Procurement) at the Inspectorate General of the Ministry of Home Affairs - Qurrotul A’yun; Dedeh Maryani; A. Masrich (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the implementation of electronic-based goods and services procurement (e-procurement) at the Inspectorate General of the Ministry of Home Affairs as part of efforts to support good governance and bureaucratic reform. George C. Edward III’s implementation theory serves as the analytical framework, emphasizing four key variables: communication, resources, disposition, and bureaucratic structure. The study employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The results indicate that the e-procurement implementation strategy within the Inspectorate General still faces several challenges, including limited human resources, inadequate internal facilities and infrastructure, the absence of internal standard operating procedures (SOPs), weak application of the reward and punishment system, and a lack of commitment and consistency in e-procurement execution. On the other hand, supporting factors include the availability of supporting application systems, sufficient internet connectivity, clear regulations, effective communication, and the benefits of time and cost efficiency. Through SWOT analysis and litmus testing of strategic issues, several improvement strategies were formulated, such as enhancing communication quality, strengthening commitment and consistency in implementing electronic procurement, reinforcing cybersecurity in the e-procurement system, improving facilities and infrastructure capacity, applying a reward and punishment system in electronic procurement practices, planning a digital risk mitigation roadmap, and establishing a rapid response team for system disruptions. With the right strategies, the Inspectorate General can become a role model in implementing efficient, transparent, and accountable electronic procurement, thereby supporting the achievement of good governance.